2022
DOI: 10.3390/ijerph20010779
|View full text |Cite
|
Sign up to set email alerts
|

Mask-Wearing and Handwashing Behaviors of Chinese Rural Residents during the Pandemic of COVID-19: A Cross-Sectional Survey

Abstract: Objective: To understand mask-wearing and handwashing behaviors of Chinese rural residents during the COVID-19 pandemic and to analyze the associated factors. Methods: This study used a multi-stage random sampling method to conduct a cross-sectional questionnaire survey during the period of July to December of 2021, in six counties located in Shandong, Shanxi, and Yunnan provinces representing the eastern, central, and western regions of China, respectively. A total of 3864 villagers were surveyed with a quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…The results of this study showed that although the accuracy rate of hand hygiene knowledge among the childcare facility staff was high—“Know that it is better to wash your hands with running water and hand sanitizer” and “Know the timing of hand hygiene” were 83.7% and 89.0%, respectively—the attitude of staff was positive too. The support rate of “Consider that the 6-step wash makes your hands cleaner” was 96.9%, the “always” practice rate of “Washed hands when coming back from public places from 2020” was 89.7%, which was consistent with the survey results of rural adults from 3 provinces in China ( 17 ), and it was higher than the rate of adult residents from Ghana (61.5%−66.5%) ( 8 ). However, the practice rate of “ Wash hands with six steps since 2020” was not high, with “always” measured at 63.0%.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The results of this study showed that although the accuracy rate of hand hygiene knowledge among the childcare facility staff was high—“Know that it is better to wash your hands with running water and hand sanitizer” and “Know the timing of hand hygiene” were 83.7% and 89.0%, respectively—the attitude of staff was positive too. The support rate of “Consider that the 6-step wash makes your hands cleaner” was 96.9%, the “always” practice rate of “Washed hands when coming back from public places from 2020” was 89.7%, which was consistent with the survey results of rural adults from 3 provinces in China ( 17 ), and it was higher than the rate of adult residents from Ghana (61.5%−66.5%) ( 8 ). However, the practice rate of “ Wash hands with six steps since 2020” was not high, with “always” measured at 63.0%.…”
Section: Discussionsupporting
confidence: 83%
“…It may be related to the trend of the pandemic, and the difference between respondents. Furthermore, washing hands with six steps needs more time, as the rate of washing at least 20 times was not high (51.7%) in rural adults from 3 provinces in China ( 17 ). This finding is similar to the responsibilities of medical workers as childcare facility staff take care of children, and their hand hygiene compliance should be improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation